Emotional intelligence as a predictor of perceived social support among spanish undergraduates - Hidalgo-Fuentes, Sergio (2021)
The goal of this research is to analyze the predictive capacity of emotional intelligence on perceived social support. 380 Psychology students completed the Trait Meta Mood Scale (TMMS-24, Salovey, Mayer, Goldman, Turvey, & Palfai, 1995) and the Multidimensional Scale of Perceived Social Support (MSPSS, Zimet, Dahlem, Zimet, & Farley, 1988). Hierarchical regression analyses show that emotional intelligence is a significant predictor of the three dimensions of perceived social support. The importance of a correctly development of the components of emotional intelligence in university students is highlighted in order to increase their perception of social support, which would have an impact on an increase in physical and psychological well-being.